Work-Related Perks, Agency Problems, and Optimal Incentive Contracts - Anthony Marino; Jan Zabojnik (Queen's University, Department of Economics, 2006)
This paper examines the effects of work-related perks, such as corporate jets and limousines, nice offices, secretarial staff, etc., on the optimal incentive contract. In a linear contracting framework, perks characterized by complementarities between production and consumption improve the trade-off between incentives and insurance that determines the optimal contract for a risk-averse agent. We show that (i) the perk may be offered even if its direct consumption and productivity benefits are offset by its cost; (ii) the perk will be offered for free; (iii) agents in more uncertain production environments will receive more perks; (iv) senior executives should receive both more perks and stronger explicit incentives; and (v) better corporate governance can lead firms to award their CEOs more perks. Our analysis also offers insights into the firms' decisions about how much autonomy they should grant to their employees and about optimal perk provision when managers and workers are organized in teams.
Keywords: J3; M5; 330; Job Perks; Agency Problems; Optimal Incentive Contracts